On-station research on draught animals: An example from Niger - Dicko, M.S. (International Livestock Centre for Africa, 1986)
Discusses the programme of the animal traction research project at ILCA-Niger. Presents results of a study undertaken to assess time saved in soil preparation by using donkeys and a pair of oxen instead of using manual labour.